Lean Manufacturing and Facilities design in Thai Automotive industries - Khemsathitanan, Chalida (2016)
Lean manufacturing is well-known principles to improve and increase the productivity and quality of the products and production. This dissertation aims to widen the knowledge of implemented Lean techniques in Thai automotive industries and how Lean influences the plant facilities design, include the strength and weakness in implementation using Survey questionnaire, interviews and factory visits to collect the practical information from professional workers in 6 automotive companies in Thailand which are Toyota Motor Thailand, Hino, Ford, Honda, Mercedes-Benz and BMW, the companies are chosen from different regions of organisation owner in order to compare and discuss the differences and similarity. Unfortunately, the lack of response from the companies leads to the research in literature based analysis combines with survey questionnaire. The research divides in two parts. The first part is comparative analysis of the implemented Lean techniques in three Asian regions countries, Malaysia, India and Thailand, based on 3 literature. The information are shown in the validity ranking in 25 Lean techniques and divided into 5 categories, then identify the most favourable techniques in the organisation. The second part is comparative and discuss of implemented Lean techniques in Thai Automotive Manufacturers, contain the information from 6 large automotive companies in Thailand which are Toyota, Nissan, Thai-Swedish assembly, Thonburi Automobile Assembly and Mercedes-Benz manufacturing Thailand, based on literature and survey questionnaire. The information are arranged into 18 Lean techniques. The analysis and discussion include comparison of differences and similarity of the information and discuss the factors that influenced the implementation levels of each method and the improvement needed in Thai Automakers.